The renaissance of fixed dose combinations: Combivir - Portsmouth, Simon D (Dove Medical Press, 2007)
Combivir is a fixed dose combination tablet of two antiretroviral drugs; zidovudine and lamivudine, used in the treatment of HIV-1 infection. AZT was the first antiretroviral used in clinical trials and the addition of lamivudine improved its effectiveness. With the introduction of highly active antiretroviral therapy in the form of a combination of three drugs including two nucleoside analogues, Combivir became the gold standard nucleoside ‘backbone’ until very recently. Combivir was the first combination agent and simplified HIV therapy greatly. The introduction of newer fixed dose combinations with the advantage of once daily dosing and improved tolerability and toxicity profiles has made Combivir a less popular choice in treatment naïve individuals needing to start therapy.